Chemical pressure induced substantial negative exchange bias on zero field cooled nanocrystalline LaFeO3. (13th January 2020) - Rao, T Lakshmana; Pradhan, M K; Chakravarty, Sujay; Dash, S
Abstract: We report a distinctly different zero feld cooled negative exchange bias(EB) effect in Ni doped LaFeO3 nanoparticle where the EB field is both temperature and concentration dependent. Nanoparticles of Ni substituted LaFeO3 is prepared by a sol-gel process. The broadening of diffraction peaks with Ni is due to the combined effect of octahedral distortion and reduction in particle size while rulling out any structural phase change. A substantial EB is acquired below spin reorientation transitions which further reduces with higher chemical pressure of Ni. EB field is found to be ∼5.71 kOe at 5 K, revealing a large value compared to similar zero field cooled EB systems. A simple model is proposed based on tunable shell-core magnetic phases to explain these unique EB effects. Present study also aimed to explore the spin and oxidation state of Fe vis a vis magnetic ordering in LaFeO3 together with consequence of Ni doping.